2019
DOI: 10.1002/hep4.1293
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Complex Concentrates for Coagulopathy in Liver Disease: Single‐Center, Clinical Experience in 105 Patients

Abstract: Patients with liver disease frequently develop coagulopathy, and fresh frozen plasma is traditionally used for correction of coagulopathy to manage and prevent bleeding. Prothrombin complex concentrates (PCCs) offer an attractive alternative because they are more readily available and avoid large‐volume transfusion. This retrospective, single‐center study reviewed clinical use of PCC in patients with acute/chronic liver disease. A total of 105 patients with 194 episodes of PCC administration were reviewed. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…A study in liver transplant patients with prolonged INR confirmed that PCC can effectively restore thrombin generation, but noted that the required doses of PCC are lower than for warfarin reversal, likely as a result of slow thrombin inhibition . A recent study confirmed the efficacy of PCC in patients with liver disease, without an excess of thrombotic events, and also observed lower dosing with PCC compared to anticoagulant reversal . Additionally, this study did not evaluate interactions with other hemostatic modalities, such as desmopressin and antifibrinolytics, and therefore may not fully reflect the multifaceted treatments that patients with thrombocytopenia may receive in clinical practice …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study in liver transplant patients with prolonged INR confirmed that PCC can effectively restore thrombin generation, but noted that the required doses of PCC are lower than for warfarin reversal, likely as a result of slow thrombin inhibition . A recent study confirmed the efficacy of PCC in patients with liver disease, without an excess of thrombotic events, and also observed lower dosing with PCC compared to anticoagulant reversal . Additionally, this study did not evaluate interactions with other hemostatic modalities, such as desmopressin and antifibrinolytics, and therefore may not fully reflect the multifaceted treatments that patients with thrombocytopenia may receive in clinical practice …”
Section: Discussionmentioning
confidence: 94%
“…32 A recent study confirmed the efficacy of PCC in patients with liver disease, without an excess of thrombotic events, and also observed lower dosing with PCC compared to anticoagulant reversal. 33 Additionally, this study did not evaluate interactions with other hemostatic modalities, such as desmopressin and antifibrinolytics, and therefore may not fully reflect the multifaceted treatments that patients with thrombocytopenia may receive in clinical practice. 34 In contrast to our ex vivo studies of spiking with PCCs, the increases in the levels of clotting factors in patients, after administration of PCCs, are variable due to redistribution of the factors to extravascular compartments, which affect the recovery and half-life.…”
Section: Discussionmentioning
confidence: 99%
“…PCC use was relatively uncommon in our study. In two small single center studies that evaluated a combined total of 33 ALF patients, PCC administration was shown to improve hemostatic parameters with a low incidence of thrombotic complications. Given the theoretical prothrombotic risks of PCC and the limited data on safety for use in ALF, further evaluation is warranted .…”
Section: Discussionmentioning
confidence: 99%
“…Fresh frozen plasma (FFP) or prothrombin complex concentrates (PCC) as treatment for active bleeding or in preparation for invasive procedure have been described for patients with ESLD not receiving anticoagulation. However, the recommended correction of therapeutic anticoagulation in the ever-more-common anticoagulated patient with ESLD undergoing liver transplantation is not well-described in literature and is varied and physician-dependent in practice (Drebes et al, 2019) as is observed in this case series from our leading transplant center.…”
Section: Introductionmentioning
confidence: 87%
“…PCC is easily reconstituted from the lyophilized form and requires no blood group specificity (Cappabiana et al, 2016). PCC likely does not increase the risk of thromboses, and has lower risk of viral transmission and volume overload than FFP (Bezinover et al, 2018;Drebes et al, 2019). Dosing is typically based on INR, however fixed-dosing strategies have been investigated (Leissinger et al, 2008;Dane et al, 2019).…”
Section: Introductionmentioning
confidence: 99%